What Does Creativity Mean in Safety-Critical Environments? - Bourgeois-Bougrine, Samira (Frontiers in Psychology, 2020)
Safety in high-risk and time-pressured situations relies on people’s ability to generate new and appropriate solutions to solve unforeseen problems for which no procedures or rules are available. This type of ability is regularly associated with the concept of creativity. While psychology researchers have studied, for decades, how creative ideas and solutions are generated, this basic research hasn’t made it into the more applied fields of human factors and neuroergonomics. Building on the research on the psychology and the neuropsychology of creativity, this paper will 1) address the question of what creativity means and what are its ties with problem solving and decision-making 2) focus on the evidence of the creative processes, the underlying mechanisms and the multiple psychological dimensions of the creative behaviour involved in unexpected events in extreme environments such as Apollo 13 mission, UAL-232 flight and Mann Gulch wildfire and 3) explore the implications for future research in the domains of neuroegonomics and differential psychology.